STUDENT’S PRONUNCIATION ERROR IN SPEAKING PERFORMANCE - Arjulayana Arjulayana; Marisol Márquez Martínez (Globish: An English-Indonesian Journal for English, Education, and Culture, 2022)
This research explores the importance of pronunciation during speaking performance. As well as what problems are naturally experienced by the students in English pronunciation. During the presentation, students experienced many obstacles in the pronunciation of both vowels and consonants. Pronunciation errors occur due to the strong influence of the mother tongue that students have and a lack of understanding in foreign language.  The sample of this research is 4th semester students of Universitas Muhammadiyah Tangerang-Indonesia. This study used qualitative analysis that contains data comparison, verification, and data presentation. The documentation method is used to obtain primary data. Primary data obtained from the results of student documentation when performed in classroom activity.